Randomised phase 3 trial: tegoprazan, a novel potassium‐competitive acid blocker, vs. esomeprazole in patients with erosive oesophagitis. Issue 7 (6th March 2019) - Lee, Kwang Jae; Son, Byoung Kwan; Kim, Gwang Ha; Jung, Hye‐Kyung; Jung, Hwoon‐Yong; Chung, Il‐Kwun; Sung, In‐Kyung; Kim, Jin Il; Kim, Jong Hyeok; Lee, Joon Seong; Kwon, Joong Goo; Park, Jung Ho; et al.
Summary: Background: Tegoprazan is a novel potassium‐competitive acid blocker that has a fast onset of action and can control gastric pH for a prolonged period, which could offer clinical benefit in acid‐related disorders. Aim: To confirm the non‐inferiority of tegoprazan to esomeprazole in patients with erosive oesophagitis (EE). Methods: In this multicentre, randomised, double‐blind, parallel‐group comparison study, 302 Korean patients with endoscopically confirmed EE (Los Angeles Classification Grades A‐D) were randomly allocated to either tegoprazan (50 or 100 mg) or esomeprazole (40 mg) treatment groups for 4 or 8 weeks. The primary endpoint was the cumulative proportion of patients with healed EE confirmed by endoscopy up to 8 weeks from treatment initiation. Symptoms, safety and tolerability were also assessed. Results: The cumulative healing rates at week 8 were 98.9% (91/92), 98.9% (90/91) and 98.9% (87/88) for tegoprazan 50 mg, tegoprazan 100 mg and esomeprazole 40 mg, respectively. Both doses of tegoprazan were non‐inferior to esomeprazole 40 mg. The incidence of adverse events was comparable among the groups, and tegoprazan was well‐tolerated. Conclusion: Once daily administration of tegoprazan 50 or 100 mg showed non‐inferior efficacy in healing EE and tolerability to that of esomeprazole 40 mg.